Tren penelitian global tentang pemikiran komputasi dalam pendidikan matematika:Analisis bibliometrik (2000–2025) - Fauziah Sumarno; Suparman Suparman; Kunti Robiatul Mahmudah (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2025)
This study aims to identify global trends, scientific collaborations, and developments in computational thinking topics in the context of mathematics education through bibliometric analysis. The method refers to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to improve transparency and quality of reporting. Data were taken from the Dimensions database for the period 2000–2025 and analyzed using VOSviewer software. The results show a significant increase in publications and citations since 2016, with the peak of publications occurring in 2023 and the highest citations in 2024. SDG 4: Quality Education is the theme most often associated with computational thinking, although contributions to Mathematics Education are still limited. The journal Education and Information Technologies is the most dominant publication medium, with researchers such as Weipeng Yang and Gary Ka Wai Wong as the main contributors. The visualization of the keyword network highlights the large focus on computational thinking skills, while mathematics education is in a peripheral position, indicating a suboptimal relationship. The visualization of co-authorship also shows the formation of strong global collaborations. The positive correlation between the number of publications and citations indicates that scientific productivity plays a major role in research visibility. These findings provide an important basis for developing further research into the integration of computational thinking into 21st century mathematics learning.